2010
DOI: 10.1039/c003710a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Pt and Pt-alloy fuel cell catalyst activity and durability via nitrogen-modified carbon supports

Abstract: Insufficient catalytic activity and durability are key barriers to the commercial deployment of low temperature polymer electrolyte membrane (PEM) and direct-methanol fuel cells (DMFCs). Recent observations suggest that carbon-based catalyst support materials can be systematically doped with nitrogen to create strong, beneficial catalyst-support interactions which substantially enhance catalyst activity and stability. Data suggest that nitrogen functional groups introduced into a carbon support appear to influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
424
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(437 citation statements)
references
References 94 publications
(151 reference statements)
12
424
0
1
Order By: Relevance
“…3a). This might arise from the presence of a large number of nitrogen atoms surrounding activated carbon atoms in the 3GN architectures, which can substantially strengthen the interaction between the metal and the support [18,19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a). This might arise from the presence of a large number of nitrogen atoms surrounding activated carbon atoms in the 3GN architectures, which can substantially strengthen the interaction between the metal and the support [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…This would activate a large number of neighboring carbon atoms and accelerate the formation of -OH by water dissociation, and thus promote oxidative removal of the adsorbed intermediate poisoning species [19,33]. The long-term stability of gC 3 N 4 -Pt nanohybrids, Pt nanoparticles on 3GN, and 20% Pt/C electrodes for methanol electrooxidation was investigated by chronoamperometric experiments at a given potential of 0.3 V in 0.5 M H 2 SO 4 + 0.5 M CH 3 OH solution (Fig.…”
Section: Articlesmentioning
confidence: 99%
“…In our case, a colloidal Pt solution was dropped onto a carbon coated TEM grid. The colloidal solution is likely to contain Pt of higher valences in the form of PtCl [2][3][4][5][6] or in citrate complexes. Guo et al 13 and Henglein 17 have observed Pt of higher valence state when using the citrate stabilized synthesis methods.…”
Section: Discussionmentioning
confidence: 99%
“…Heteroatom functional groups introduced into carbon support appear to influence not only the active sites of the carbon support, which results in smaller catalyst particle size and increased catalyst particle dispersion, but also increases support/catalyst chemical binding (or "tethering"), which in turn results in enhanced stability of the catalysts. Furthermore, the metallic NPs electronic structure is modified, which enhances intrinsic catalytic activity [14]. In spite of these advantages, developing new heteroatom functionalities for modification of the carbon materials that provide well-dispersed noble metal NPs are still desirable.…”
Section: Introductionmentioning
confidence: 99%